83.0k views
4 votes
The function f(x) = x2 + 6x + 3 is transformed such that g(x) = f(x − 2). Find the vertex of g(x).

2 Answers

5 votes

Answer:

(-5,-6)

Explanation:

just took the test and got it right

User KevinUK
by
6.2k points
5 votes

Answer:

(-1,-6)

Explanation:


f(x)=x^2+6x+3


g(x)=f(x-2)


g(x)=(x-2)^2+6(x-2)+3 (Replaced x in f with (x-2))


g(x)=x^2-4x+4+6x-12+3 (Used
(x+b)^2=x^2+2bx+b^2 and distributive property)


g(x)=x^2-4x+6x+4-12+3 (Gathered like terms)


g(x)=x^2+2x-5 (Simplified)

The vertex of a parabola occurs at
((-b)/(2a),g((-b)/(2a)).

Let's find
(-b)/(2a) first.


(-2)/(2(1))=-1

Now we can obtain
g((-b)/(2a)) which is
g(-1) in this case:


g(x)=x^2+2x-5


g(-1)=(-1)^2+2(-1)-5


g(-1)=1-2-5


g(-1)=-1-5


g(-1)=-6.

The vertex is (-1,-6).

User Supra
by
5.5k points